A arqueologia de uma Babel moderna: fundamentos histórico-filosóficos da Política Nacional de Humanização (PNH) - Miguel, Roberto Pereira [UNIFESP] (2014)
Objective: In this paper, we set out to investigate the historical and philosophical foundations of the National Policy of Humanisation (PNH) in Brazil. We are interested in not just the most striking aspects of the policy, but especially in those points that are still implicit in such a project and which lack investigation and investment. Methodology: We undertook this task by reading the documents produced by the Ministry of Health that are related to the theme of the humanisation of healthcare, and analyzing the works and articles written and published both by intellectuals directly involved in the construction of this policy and by researchers dedicated to the study of this initiative. We seek to interpret these results from the perspective of the thought of two exponents of the conservative philosophical tradition: Michael Oakeshott and Theodor Dalrymple. Results: The results show the modern philosophical foundation of PNH, of which we highlight: 1) the rationalist character of the policy, from the assumption that political and social engineering would be able to reform the world and man; 2) the historical materialism of Karl Marx, from the perception that the problematic named ?dehumanisation? is derived from the precarious conditions of the work processes; 3) its anthropological basis anchored in the notion of ?perfectibility?, which supports the idea that it is possible to manage emotions, stimulate solidarity, and produce ?new subjects? and ?new subjectivities? through the PNH. Conclusion: These elements allow us to designate PNH as Politics of Faith, according to Oakeshott, which is always susceptible to the last plans of better towers of Babel. Faith here, as opposed to the traditional religious faith, is faith in the ability of human beings to perfect themselves through their own efforts from the discovery of methods to continuously spread the power of government as an essential tool for controlling the design and improvement of individuals and groups. Like the original Babel, resentment and the hybris of the entrepreneurs are both the main engine of its construction, and the primary reason for its failure.